Dissemination Of Indonesia : A Textual Analysis On The Construction Of Indonesia In Selected Print Media For Youth Readership - R.d Safrina (Jurnal Sosioteknologi, 2007)
With reference to Homi Bhabha"Ÿs concept of dissemination (1994) which suggests that the writing of a nation is a double-writing constructed from pedagogical and performative discourses with the possibility of generating tensions which question the symbolic formation of modern social authority, the study examines the dissemiNation of Indonesia in Indonesian print media with a specific youth readership by highlighting the question on the possible symbolic formation(-s) of modern social authority. The analysis focuses on specific Indonesian historical contexts such as the Independence Day and is anchored on questions which dig into the prevailing pedagogical and performative texts and explore the meanings from such dissemination. The findings indicates the dynamic negotiations on the idea of nation. These idea(-s) stem from prevailing discourses in the society that might have overtly or covertly manifested in the selected texts. Historical narratives backgrounding the selected texts evidence the pedagogic discourses made available for the readers which intertwine with performative discourses reflecting the forces of globalization and popular culture. Keywords: dissemination, nation, identity, local, global, youth, pop culture